Severe Hypocalcemia and Transient Hypoparathyroidism After Hyperthermic Intraperitoneal Chemotherapy - Tharmalingam, Senthuran; Reddy, Sanjay; Sharda, Pankaj; Koch, Christian A. (Hormone and Metabolic Research, 2020)
Dear Editors,Hypocalcemia is not unusual in patients hospitalized for critical illness and has also been described after general surgery in addition to head and neck surgical procedures 123. Hypocalcemic events commonly occur in the setting of massive blood transfusion, albumin deficiency, vitamin D deficiency, and/or hypomagnesemia. In the absence of these factors, only slight decreases in calcium levels within the normal range have been reported during surgical procedures 1. Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) causing asymptomatic hypocalcemia has only been reported in two previous studies 45. The etiology is unclear. We here report a patient who developed severe symptomatic hypocalcemia likely as a result of a profound inflammatory reaction with transient hypoparathyroidism after HIPEC.